Effects of Ribosomal Protein S10 Flexible Loop Mutations on Tetracycline and Tigecycline Susceptibility of Escherichia coli - Izghirean, Norbert; Waidacher, Claudia; Kittinger, Clemens; Chyba, Miriam; Koraimann, Günther; Pertschy, Brigitte; Zarfel, Gernot (Frontiers in Microbiology, 2021)
Tigecycline is a tetracycline derivative that is being used as antibiotic of last resort. Both tigecycline and tetracycline bind to the small (30S) ribosomal subunit and inhibit translation. Target mutations leading to resistance to these antibiotics have been identified both in the 16S ribosomal RNA and in ribosomal proteins S3 and S10 (encoded by the rpsJ gene). Several different mutations in the S10 flexible loop tip residue valine 57 (V57) have been observed in tigecycline resistant Escherichia coli (E. coli) isolates. However, the role of these mutations in E. coli has not yet been characterized in a defined genetic background. In this study, we chromosomally integrated ten different rpsJ mutations into E. coli, resulting in different exchanges or a deletion of S10 V57, and investigated the effects of the mutations on growth and tigecycline/tetracycline resistance. While one exchange, V57K, decreased the MIC (Etest) to tetracycline to 0.75 µg/ml (compared to 2 µg/ml in the parent strain) and hence resulted in hypersensitivity to tetracycline, most exchanges, including the ones reported previously in resistant isolates (V57L, V57D, V57I) resulted in slightly increased MICs to tigecycline and tetracycline. The strongest increase was observed for the V57L mutant, with a MIC (Etest) to tigecycline of 0.5 µg/ml (compared to 0.125 µg/ml in the parent strain) and a MIC to tetracycline of 4.0 µg/ml. Nevertheless, none of these exchanges increased the MIC to the extent observed in previously described clinical tigecycline resistant isolates. We conclude that, next to S10 mutations, additional mutations are necessary in order to reach high-level tigecycline resistance in E. coli. In addition, our data reveal that mutants carrying S10 V57 exchanges or deletion display growth defects and, in most cases, also thermo-sensitivity. The defects are particularly strong in the V57 deletion mutant, which is additionally cold-sensitive. We hypothesize, that the S10 loop tip residue is critical for the correct functioning of S10. Both the S10 flexible loop and tigecycline are in contact with helix h31 of the 16S rRNA. We speculate that exchanges or deletion of V57 alter the positioning of h31, thereby both influencing tigecycline binding and S10 function.